LITERATUR REVIEW: TERAPI OKUPASI PADA ANAK TUNAGRAHITA - Umi Luthfiyah; Puput Prilla Santika; Embun Suri; Tika Sahputri (CV. Denasya Smart Publisher, 2025)
This study is to identify occupational therapy for Tunagrahita children. The purpose of writing this article is to use the literature review method, which describes the theories, findings and other research materials. The results showed that occupational therapy for children with disabilities has a good effect. The application of occupational therapy in daily life begins with determining the goals of therapy, for example, daily activities that are expected to enable children to use music therapy, buttoning clothes, caring for clothes, and making their own handicrafts.